Production Of Cellulase And Xylanase By Indigenous Aspergillus Niger Ai-1 Via Solid Substrate Fermentation And Its Application In Deinking Of Mixed Office Waste Paper - Pang , Pei Kheng (2010)
The present work focused on the production of cellulases and xylanase using Aspergillus niger AI-1 via solid substrate fermentation and its application in enzymatic deinking of mixed office waste paper. A total of 25 out of 70 fungal isolates representing the genera of Aspergillus, Penicillium, Trichoderma, and Mucor were selected based on the hydrolysis zone observed in CMC and oat spelt agar plates. They were also selected based on their high cellulases and xylanase activity. Solid substrate fermentation was carried out using these fungal isolates and local agricultural wastes consisting of sugar cane bagasse, palm kernel cake, rice husk and wood dusts were used as substrate. Among them, 3 fungi isolates were selected based on the highest enzymes production on SSF using the mixture of sugar cane bagasse and palm kernel cake as substrate.